Sickle cell disease in Cape Town: a perspective from two regional hospitals - Vahed, Anisa (Department of Paediatrics and Child Health, 2022)
Background: Inherited hemoglobinopathies are a global health burden. Sickle cell disease (SCD) is the most common genetic disorder of haemoglobin in Africa but is uncommon in the South African population. Objectives This study aimed to describe the presentation and experience managing paediatric patients with SCD at two regional hospitals in Cape Town. Methods This retrospective study used routine data of children aged 0-13 years with SCD managed at New Somerset and Victoria Hospitals in Cape Town from January 2010 to December 2018. Data analysed included demographics, diagnosis, out- and in-patient episodes, and the need for transfers to tertiary level. Results We identified 63 patients of which three did not fit the study criteria and four had missing clinical records. Of the 56 children included, most were diagnosed at the regional hospital (n=32 [58%]) and only a third (n=18 [32%]) were down-referrals from tertiary level facilities. The annual number of new patients per year varied with the most in 2009 and 2015. The median age at first presentation was 20.1 months (interquartile range [IQR] 7.1-43.9 months). There was a male predominance. The majority (n=39 [67%]) were born in South Africa, eleven were born in the Democratic Republic of Congo (DRC) and six in other African countries. None of the parents were born in South Africa. The majority of parents were from DRC (73/110) and Nigeria (11/110). Approximately one third (39%) of patients had a family history of SCD and a quarter (25%) had an affected sibling. Most children were diagnosed incidentally via full blood count findings (66%); others presented with symptomatic anaemia (28%) or were screened because of an affected sibling (11%). The mean number of hospital days was 3.0 (range 0-13). Infections, bone crises and symptomatic anaemia accounted for the majority of hospital admissions. Referral for tertiary level care occurred in 23/56 (41%) patients with most requiring specialist opinion from haematology and/or other specialist disciplines. Nine (16%) children were lost to follow-up, one was transferred to another province and one died at another institution. Conclusion An increasing number of children diagnosed with SCD are being seen in health facilities in Cape Town and probably other parts of South Africa due to migration and children being born to families with SCD ancestries. Recognising the presentation and complications of SCD and developing competency at all levels of care in providing appropriate, protocolised management are important to reduce morbidity and mortality among children with SCD in our setting